Factors affecting the productivity of maize (Zea mays L.) in selected areas of Bangladesh: Factors affecting the productivity of maize - Sampa, Asma Yeasmin; Alam, Md Ariful; Sammy, Hasan Mahammad (SAARC Journal of Agriculture, 2022)
Though the production of maize and the area under cultivation has accelerated, the rate of increase in production is not satisfactory due to its increasing demand with the continuous expansion of the dairy and poultry sectors in Bangladesh. The intended study aimed to identify the factors affecting the production of maize and whether the resources were utilized optimally in the production process. Required data were gathered from 130 maize growers, who were taken through simple random sampling from two districts, Manikganj and Rajshahi, of Bangladesh, through the interview with a pretested questionnaire. The impact of several factors on the productivity of maize was computed with the help of the Cobb-Douglas production function. The study revealed a significant positive impact of seed, land preparation, fertilizer and water management on the final output of maize. Although maize cultivators earned a decent profit, inefficient uses of resources were practiced. Seed and fertilizer were underutilized while labour was over-utilized in the production process. The sampling frame was selected purposively to represent the intensive maize producing area. Farmers shifted to maize cultivation progressively but the high price of seeds, natural calamities and low price of grains may affect production in future. SAARC J. Agric., 20(2): 93-104 (2022)